Heterologous Boost Following Mycobacterium bovis BCG Reduces the Late Persistent, Rather Than the Early Stage of Intranasal Tuberculosis Challenge Infection - Wu, Yaqi; Cai, Ming; Ma, Jilei; Teng, Xindong; Tian, Maopeng; Bassuoney, Eman Borham Mohamed Borham; Fan, Xionglin (Frontiers in Immunology, 2018)
Adults are the leading population affected by tuberculosis (TB) epidemic and death. Developing an effective vaccine against adult TB is urgently needed. Mycobacterium bovis Bacillus Calmette-Guerin (BCG) prime-heterologous boost strategy has been explored extensively to protect adults against primary TB infection, but the majority of experimental regimens have not improved the protection primed by the BCG vaccine. The reason attributed to the failure remains unknown. In this study, CTT3H-based vaccines, namely DMT adjuvanted CTT3H subunit or DNA vaccine (pCTT3H-DMT), and recombinant adenovirus rAdCTT3H were constructed. Protective efficacy and immunogenicity of BCG prime-CTT3H based boosters were compared in C57BL/c mice models of primary or late persistent TB infection. Similar protective efficacy against early intranasal infection was provided by different CTT3H-based vaccines alone in vaccinated mice, and their protection was inferior to that of the BCG vaccine. In addition, CTT3H-based heterologous boosters did not enhance the protection conferred by the BCG vaccine against primary infection. However, all of these three boosters provided stronger protection against late persistent TB infection than BCG alone, regardless of vaccine types. Although BCG prime-boosters elicited Th1-biased responses to the antigen CTT3H, the number of CTT3H-sepcific IFN-γ-expressing TEM (CD62LloCD44hi) and IL-2-expressing TCM (CD62LhiCD44hi) cells in the spleen was not improved before exposure to M. tuberculosis infection. In contrast, IFN-γ+ TEM and IL-2+ TCM cells in spleens, especially in lungs were significantly increased in BCG prime-boosters after exposure vaccination. Our results indicate that BCG prime-boost strategy might be a promising measure for the prevention against late persistent TB infection by induction of IFN-γ+ TEM and IL-2+ TCM cells in the lung, which can be used as alternative biomarkers for guiding the clinical practice and future development of TB vaccine for adults.